(untitled) (JURNAL KEPERAWATAN, 2022)
Puskesmas is one of the health service facilities that is the mainstay or benchmark of health development, a means of community participation, and the first comprehensive service center of an area. The purpose of this study was to determine the factors that influence the utilization of the services of the Puskesmas Assistant in the working area of the Pigs Dayun Community Health Center. This type of research is a quantitative study with a research design used cross sectional research design with a total sample of 63 people. Analysis of the data used bivariate analysis. The results showed that there was a significant relationship between knowledge factors (p value 0.004), attitudes (p value 0.002), and access (p value 0.049) to the utilization of Supporting Health Centers. It is recommended to the Puskesmas to optimize the utilization of the Supporting Puskesmas through the socialization of programs that are arranged regularly